2021
DOI: 10.1097/eja.0000000000001633
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and hypnosis for anxiety and pain management in intensive care units

Abstract: BACKGROUND Virtual reality and hypnosis are little studied in complex contexts, such as intensive care, where patients need significant physical and psychological assistance. OBJECTIVES To compare and combine hypnosis and virtual reality benefits on anxiety and pain on patients before and after cardiac surgery. DESIGN Prospective randomised controlled clinical trial. SETTING The study was conducted in the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
2
43
3
1
Order By: Relevance
“…[ 9 , 10 ]. However, there were no significant differences in the pre-defined outcome measures (anxiety, pain, fatigue, relaxation, physiological parameters, and opioid use) [ 11 ]. Further studies are required to investigate potential beneficial effects, and cost-effectiveness.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 10 ]. However, there were no significant differences in the pre-defined outcome measures (anxiety, pain, fatigue, relaxation, physiological parameters, and opioid use) [ 11 ]. Further studies are required to investigate potential beneficial effects, and cost-effectiveness.…”
Section: Main Textmentioning
confidence: 99%
“…In conclusion, many studies suggest a positive effect of VR on stress, anxiety, and delirium in critically ill patients. To date, the largest, prospective, randomised-controlled trials in this area have shown neutral [ 11 ] or positive [ 3 ] results.…”
Section: Main Textmentioning
confidence: 99%
“…Among RCTs, one assessed the type of computer-generated video (urban versus mountain world versus a video displayed on the bedroom-TV screen) on 45 patients, reporting a better restoration feeling with the mountain world [ 48 ], consistently with findings of the present study that highlights a different impact of VR related to device characteristics. Three RCTs included 48(24/group) [ 49 ], 100(25/group) [ 50 ], and 200(100/group) [ 51 ] post-cardiac surgery patients. VR improved significantly sleep [ 49 ] and relaxation [ 50 ] but failed to improve anxiety and pain at rest [ 50 ] or during chest drain removal [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three RCTs included 48(24/group) [ 49 ], 100(25/group) [ 50 ], and 200(100/group) [ 51 ] post-cardiac surgery patients. VR improved significantly sleep [ 49 ] and relaxation [ 50 ] but failed to improve anxiety and pain at rest [ 50 ] or during chest drain removal [ 51 ]. In the latter study, VR was compared to nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Rousseaux et al in a randomised controlled trial of 100 patients, tested the use of "virtual reality hypnosis" in patients one day before and one day after cardiac surgery. In this small study, there were no significant differences with regards to the outcome measures (anxiety, pain, fatigue, relaxation, physiological parameters, and opioid use) [ 8 ]. A randomised controlled trial of 48 patients evaluated the positive effects of VR on the quality of sleep in ICU patients: VR resulted in a significantly better sleep quality, although total sleep time and light sleep time did not differ between the groups [ 9 ].…”
Section: A Non-pharmacological Way Of Treating Anxiety Stress and Pain?mentioning
confidence: 99%